A step-by-step guide to creating an academic surgery interest group: Review article. (September 2021) - Domínguez-Alvarado, Gonzalo; Villar-Rincón, Karla; Castillo-Miranda, María; Quintero-Díaz, Angie; Ramírez-Rangel, Angie; Lozada-Martínez, Ivan David; López-Gómez, Luis; Bolaño-Romero, Maria Paz; Rahman, Sabrina
Abstract: An academic interest group in medicine is defined as a collective that can be made up of undergraduate students, residents, and/or teachers, who share as an object of interest the advancement and growth of a specific area of medicine. It is organized to carry out extracurricular academic and research activities. It is essential to stimulate participation in these interest groups, which allow the personal and professional growth of their members, being a tool that promotes and provides better opportunities for entry as candidates for graduate studies. The American College of Surgeons is one of the largest medical scientific societies with the participation of undergraduate students with an interest in surgery. This society mentions the benefits of participating in interest groups in surgery, specifically, it highlights the importance of contributing to these when looking for a surgical specialty, because they address issues such as: what is the mentioned specialty itself?, what are the details about the application process for each surgical specialty?, these groups can provide information on different residency programs, lifestyle benefits, and/or cons; in addition to improving practical skills through surgical technique workshops or various organized activities. Based on the above, the objective of this manuscript is to design a Step-by-step guide for the creation of a surgical interest group, in order to encourage participation by medical students, residents, and teachers in the research and academic field. Highlights: An academic interest group in surgery reinforces skills and knowledge. An academic interest group in surgery can be coordinated by undergraduate students. Academic interest groups in surgery generate national and international knowledge networks.